2010
DOI: 10.1093/humrep/deq089
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive or non-consecutive recurrent miscarriage: is there any difference in carrier status?

Abstract: The sequence of preceding pregnancies is not a risk factor for carrier status. Therefore, couples with miscarriages interspersed with healthy child(ren) should be managed the same as couples with consecutive miscarriages regarding chromosome diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Fifteen percent of pregnancies end in a miscarriage and 1% of women who achieve pregnancy will experience recurrent pregnancy loss (RPL), defined as three or more miscarriages23. When a pregnancy fails at the embryonic preimplantation stage, before it is clinically recognized, it presents as primary infertility.…”
mentioning
confidence: 99%
“…Fifteen percent of pregnancies end in a miscarriage and 1% of women who achieve pregnancy will experience recurrent pregnancy loss (RPL), defined as three or more miscarriages23. When a pregnancy fails at the embryonic preimplantation stage, before it is clinically recognized, it presents as primary infertility.…”
mentioning
confidence: 99%
“…Jaslow et al reported that the prevalence of abnormal results for ''evidence-based'' and ''investigative'' diagnostic tests did not differ among women with two, three, or four or more pregnancy losses (4). Van den Boogaard et al reported that consecutive versus nonconsecutive miscarriages did not impact the frequency of being a carrier of a structural chromosome abnormality in couples with two or more pregnancy losses (5). Therefore, the investigators recommended couples with two or more pregnancy losses interspersed with healthy children be managed in the same way as couples with two or more consecutive miscarriages.…”
mentioning
confidence: 99%
“…Overall, cytogenetic abnormalities (including fetal aneuploidy or polyploidy) are found in 50% to 70% of spontaneous abortion specimens arising from natural conceptions [20,21]. Indeed, some authors explain spontaneous miscarriages as a 'physiological' phenomenon, which prevents conceptions affected by chromosomal aberrations incompatible with life from progressing to viability [4,11].…”
Section: Genetic Abnormalities Embryonic Chromosomal Abnormalitiesmentioning
confidence: 99%